Queue length and waiting time distributions in a system of M dependent queues / Soo Huei Ching - Soo, Huei Ching (2012)
Consider a system of M Hypo(2)/Hypo(2)/1 queues of which the dependence relation is specified via an interaction scheme. Two types of interaction scheme are considered. We proposed a method for deriving the stationary joint queue length distributions, and the stationary waiting time distribution, of a customer seeking service in a given queue. The proposed method has also been adapted to find the stationary joint queue length distribution in a system of two dependent Hypo(2)/Hypo(2)/c/c queues. The numerical results found by using the proposed method agree well with those based on simulation.